2014
DOI: 10.1111/1541-4337.12106
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Compounds and Plant Phenolic Extracts as Natural Antioxidants in Prevention of Lipid Oxidation in Seafood: A Detailed Review

Abstract: Lipid oxidation is the principal cause of quality loss in seafood, which is known to contain high amounts of polyunsaturated fatty acids. Such quality deterioration, associated with the development of off-flavor as well as lowering of nutritive value, can be retarded by incorporation of additives having antioxidative properties. The use of synthetic antioxidants has long been practiced in retarding lipid oxidation. However, due to the potential health concerns of synthetic antioxidants, polyphenolic compounds,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
151
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 244 publications
(160 citation statements)
references
References 129 publications
5
151
0
4
Order By: Relevance
“…This is consequence of their well-known ability of scavenging a wide 167 range of both reactive oxygen species (ROS) and reactive nitrogen species (RNS) such 168 as superoxide, hydroxyl, peroxyl, and alkoxyl radicals, and peroxynitrous and 169 hypochlorous acids (Maqsood, Benjakul, Abushelaibi, & Alam, 2014). The reaction is 170 produced by donation of a hydrogen atom to the radical at the same time that the 171 phenolic compound is converted into a phenolic free radical according to equation 6 172 (AH is the phenolic compound).…”
Section: The Free Radical-scavenging Ability Of Phenolic Compounds 164mentioning
confidence: 99%
“…This is consequence of their well-known ability of scavenging a wide 167 range of both reactive oxygen species (ROS) and reactive nitrogen species (RNS) such 168 as superoxide, hydroxyl, peroxyl, and alkoxyl radicals, and peroxynitrous and 169 hypochlorous acids (Maqsood, Benjakul, Abushelaibi, & Alam, 2014). The reaction is 170 produced by donation of a hydrogen atom to the radical at the same time that the 171 phenolic compound is converted into a phenolic free radical according to equation 6 172 (AH is the phenolic compound).…”
Section: The Free Radical-scavenging Ability Of Phenolic Compounds 164mentioning
confidence: 99%
“…Previously, it was reported that lycopene supplementation could increase total antioxidant capacity in liver of breeding hens [5]. Phenolic compounds were also noted could delay oxidation in fish oil [6]. In addition, ascorbic acid supplementation could decrease serum malondialdehyde (MDA) concentration in broiler [7].…”
mentioning
confidence: 99%
“…Ponce et al (2004) demonstrated the effectiveness of several essential oils including tea tree in reducing peroxidase activity of leafy vegetables by in vitro assays. Moreover, gallic acid is a natural phenolic compound extractable from plants, especially green tea and grapes and its antioxidant properties were well demonstrated (Lu et al, 2006, Maqsood et al, 2014.…”
Section: Evolution Of Pod Activity On Mixed Vegetables and Individualmentioning
confidence: 99%